2003
DOI: 10.1002/aic.690491203
|View full text |Cite
|
Sign up to set email alerts
|

Gas and liquid distribution in the monolith film flow reactor

Abstract: The gas-liquid distribution in a monolith film flow reactor is in®estigated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 14 publications
3
47
0
4
Order By: Relevance
“…Since the effect of small variations in the channel flow rates on the conversion is nearly linear, the higher conversion in channels with a lower flow rate compensates for the channels with a higher flow rate. This result does not imply that a proper design of the flow distribution manifolds is not important: a bad design can actually result in large flow deviations ( r F > 0.3), which do have an effect on the reactor performance [12]. The method presented here is useful in defining a limit on what flow distribution is to be considered adequate and beyond which point improvements in the flow distributor no longer have an effect on the reactor performance.…”
Section: Reactor Conversionmentioning
confidence: 37%
See 1 more Smart Citation
“…Since the effect of small variations in the channel flow rates on the conversion is nearly linear, the higher conversion in channels with a lower flow rate compensates for the channels with a higher flow rate. This result does not imply that a proper design of the flow distribution manifolds is not important: a bad design can actually result in large flow deviations ( r F > 0.3), which do have an effect on the reactor performance [12]. The method presented here is useful in defining a limit on what flow distribution is to be considered adequate and beyond which point improvements in the flow distributor no longer have an effect on the reactor performance.…”
Section: Reactor Conversionmentioning
confidence: 37%
“…Due to the small volume of a single channel, many parallel channels have to be used to obtain sufficient production, which makes uniform distribution of the reaction mixture over thousands or even millions of channels necessary [11]. Since flow maldistribution can affect the reactor performance [12,13], several authors have presented design studies of flow distribution manifolds [14±17]. However, besides the design of the flow distributor, also manufacturing tolerances on, for example, the diameter of the microchannels and the applied amount of catalyst coating and issues like channel blockage influence the flow distribution [8,18].…”
Section: Introductionmentioning
confidence: 40%
“…It was introduced by Hoek et al [24] and used in various studies before [5,10,13,25,26]. A discretized form of this coefficient applied in the current work is given in Eq.…”
Section: Experimental Workmentioning
confidence: 47%
“…The authors demonstrated that the ITS method is a viable technique for studying two-phase flows in large-scale monolith reactors. In another study, magnetic resonance imaging (MRI)-based tomography was applied by Heibel et al [20] to study the gas-liquid distribution in a monolith film flow reactor. As compared with the above-mentioned expensive methods, Behl et al [21] developed a conventional collecting technique to measure the liquid distribution across the monolith cross-section.…”
Section: Introductionmentioning
confidence: 47%